Assessments of right ventricular strain using cardiac magnetic resonance imaging following kidney transplantation. Issue 4 (23rd December 2021) - Cai, Sean; Mahmood, Tahrin; Hashi, Abdulaziz Ahmed; Prasad, Ramesh; Connelly, Philip W.; Connelly, Kim A.; Wald, Ron; Deva, Djeven P.; Yan, Andrew T.
Abstract: Although kidney transplantation (KT) has been shown to ameliorate adverse left ventricular (LV) remodelling associated with end stage kidney disease, its effects on the right ventricle have not been well studied. Recently, strain imaging has been shown to be a sensitive measure of early subclinical myocardial dysfunction. Using cardiac magnetic resonance imaging (MRI), we examined the effects of KT on right ventricular (RV) strain parameters. In a cohort of 81 patients (39 patients underwent KT and 42 patients remained on dialysis as control group), cardiac MRI studies were obtained at baseline and at 1 year follow‐up. There were no significant differences in RV strain values between the groups at baseline. After 1 year, RV strain values did not significantly change in patients who received KT, and changes in RV strain over 1 year were not significantly different between the KT and the dialysis groups. Given the previously demonstrated improvement in LV strain post‐KT, the current study suggests that RV and LV remodelling post‐KT may have different mechanisms. Further studies elucidating the effects of KT on RV remodelling are needed. SUMMARY AT A GLANCE: In this prospective cohort study, the authors compared changes over time in right ventricular (RV) strain using cardiac MRI in dialysis patients who did and did not receive a kidney transplant. They found that RV strain measures did not change over time, suggesting that cardiac remodelling after transplant likely occurs via other mechanisms.